Telephone calls in Gianfranco Rosi’s Fire at Sea (Fuocoammare, 2016) - Wilson, Emma (Alphaville, 2019)
The Hollywood Reporter feature on Gianfranco Rosi’s Fire at Sea (Fuocoammare, 2016) reads: “Where journalism leaves off, Fire at Sea begins”. The director spent months living alone on Lampedusa looking for ways to film the current refugee tragedy in the Mediterranean. The poetic film that he made (and that won the Golden Bear at Berlin) is an indirect reckoning with its subject, and, I argue no less political for this. Referring to the work of Adriana Cavarero, Christina Sharpe, Anne Dufourmantelle and Judith Butler, this article explores the uses of recorded telephone calls and other transmitted voices and songs in the film. These calls and voices offer forms of appeal and aural, non-visual, but bodily, affective traces. The film emphasises the political importance of listening, and of attending to these calls and voices, envisaging a mesh of connectedness, of threads of human attachment.